1987
DOI: 10.1128/jb.169.1.224-230.1987
|View full text |Cite
|
Sign up to set email alerts
|

Insertion-sequence-dependent rearrangements of Pseudomonas cepacia plasmid pTGL1

Abstract: Pseudomonas cepacia 249 (ATCC 17616) harbors a 170-kilobase (kb) plasmid designated pTGL1. We identified three insertion sequences, IS405, IS408, and IS411, on this plasmid. Various prototrophic and auxotrophic derivatives in our collection contained variants of pTGL1 formed by accretion and deletion of other elements. Plasmid pTGL6, the variant in one prototroph, evolved from pTGL1 by the addition of three copies of IS401 (1.3 kb) and one of IS402 (1 kb), to generate pTGL5, and recombination between two of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 37 publications
(39 reference statements)
0
29
0
Order By: Relevance
“…As far as gram-negative bacteria are concerned, most IS elements have been isolated from enteric bacteria (mainly E. coli; for reviews and lists of isolated elements, see references 14 and 20). However, there have been a substantial number of reports on IS elements identified in other gram-negative bacterial species, such as Agrobacterium tumefaciens (3,15,24,42), Xanthomonas campestris (22, 23), and various Rhizobium (9,28,32) and Pseudomonas (6,13,35,41,45) strains.In general, these elements have been found more or less by chance because of the capacity to inactivate or activate particular genes. However, there have been successful attempts to screen for transposable elements by means of direct selection procedures (8,15,30,35).…”
mentioning
confidence: 99%
“…As far as gram-negative bacteria are concerned, most IS elements have been isolated from enteric bacteria (mainly E. coli; for reviews and lists of isolated elements, see references 14 and 20). However, there have been a substantial number of reports on IS elements identified in other gram-negative bacterial species, such as Agrobacterium tumefaciens (3,15,24,42), Xanthomonas campestris (22, 23), and various Rhizobium (9,28,32) and Pseudomonas (6,13,35,41,45) strains.In general, these elements have been found more or less by chance because of the capacity to inactivate or activate particular genes. However, there have been successful attempts to screen for transposable elements by means of direct selection procedures (8,15,30,35).…”
mentioning
confidence: 99%
“…The genome of this bacterium contains a large number of insertion sequences (ISs) (25,27), which were identified on the basis of their abilities to promote genomic rearrangements (4,12) and to activate the expression of neighboring genes (15,43,60). Such elements have been implicated in the recruitment of foreign genes for novel catabolic functions (15,43,54,60).…”
mentioning
confidence: 99%
“…Southern blotting performed with chromosomal digests of B. cepacia AC1100, 17616 (249) and 25416 and E. coli JM109 showed that the new IS elements and IS931 were observed only in B. cepacia AC1100 (data not shown). Additionally, no homology to the genomic DNA of AC1100 was detected by using several IS elements isolated from B. cepacia 17616 (IS401, IS402, and IS408 [6,17,18,36]) as DNA probes. These results suggest the presence of a wide diversity of IS elements among isolates of B. cepacia.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of IS elements in B. cepacia strains have been identified on the basis of their capability to insertionally activate downstream genes (6,17,18,30,36). Two IS elements that increase the expression of neighboring genes, IS931 and IS932, have been isolated previously from strain AC1100.…”
Section: Resultsmentioning
confidence: 99%